The Domestication and the Foreignization in Translating Poetics in the Poetry of Alkhansa to the French Language by Victor De Coppier - Boucherit, Jawhara; Boukrika, Ammar (Journal of Human Sciences, 2020)
Poetics did not prevent the orientalist Victor de Coppier from daring translating the poetry of AlKhansa where it included the rhetoric, the rhythm, the imagination and the symbols in order to engender in the spirit and in the mind of the receiver different sensations and emotions. So, the attainment of the meaning of the poetic image, its beautiful presentation and its intense effect is judged so difficult. We try through this research to show two methods used to translate the Arabic poetics to the French language; The domestication and the foreignization and the consequences of this act of translating.